2022
DOI: 10.3390/nano12071062
|View full text |Cite
|
Sign up to set email alerts
|

Physical Properties and the Reconstruction of Unstable Decahedral Silver Nanoparticles Synthesized Using Plasmon-Mediated Photochemical Process

Abstract: Plasmon-mediated shape transformation from quasi-spherical silver nanoparticles (AgNPs) to silver nanoprisms (AgNPrs) and decahedral silver nanoparticles (D-AgNPs) under irradiation of blue LEDs (λ = 456 ± 12 nm, 80 mW/cm2) was studied at temperatures ranging between 60, 40, 30, 20, 10, and 0 °C. It was found that reaction temperature affected transformation rates and influenced the morphology distribution of final products. The major products synthesized at temperatures between 60 °C and 0 °C were AgNPrs and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 51 publications
(77 reference statements)
0
5
0
Order By: Relevance
“…Then the photochemical seed AgNP colloids were irradiated with blue LEDs (460 ± 12 nm, 40 mW/cm 2 , as shown in Figure 1B) for 90 min. The end products exhibited a fascinating bicolor characteristic, reflecting shades of orange and green when viewed from various angles [28], as illustrated in Figure 2. This intriguing optical property is attributed to the intense light scattering by the product's unique structure [29,30].…”
Section: Preparation Of D-agnp Colloids Using the Photochemical Methodsmentioning
confidence: 99%
“…Then the photochemical seed AgNP colloids were irradiated with blue LEDs (460 ± 12 nm, 40 mW/cm 2 , as shown in Figure 1B) for 90 min. The end products exhibited a fascinating bicolor characteristic, reflecting shades of orange and green when viewed from various angles [28], as illustrated in Figure 2. This intriguing optical property is attributed to the intense light scattering by the product's unique structure [29,30].…”
Section: Preparation Of D-agnp Colloids Using the Photochemical Methodsmentioning
confidence: 99%
“…For instance, after Kneipp first used colloidal silver nanoparticle solution to detect a single R6G molecule in 1997 [ 101 ], subsequent studies have demonstrated the achievement of single-molecule detection using nanometal colloids. As a result, ongoing efforts focus on the development of metal nanoparticles, including different shapes of MNPs [ 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 ], composite materials of MNPs [ 111 , 112 , 113 , 114 , 115 ], and the modified MNPs [ 116 , 117 , 118 ].…”
Section: Design Fabrication and Applications Of Sersmentioning
confidence: 99%
“…Currently, various shapes of metal MNPs have been proposed, including the nanorods [ 111 , 116 ], nanostars [ 109 ], nanocubes [ 110 ], hyperbranched Au nanocorals [ 102 ], flower-like Au NPs [ 103 ], Pt-Au triangular nanoprisms [ 104 ], Au popcorns [ 105 ], decahedral Ag NPs [ 106 ], Au nanofoams [ 107 ], and dual-gap Au nanodumbbells [ 108 ]. These different shapes are aimed at creating more branches, pores, or tips on the MNPs, which are believed to generate high-intensity electromagnetic regions, also known as anisotropic hot spots.…”
Section: Design Fabrication and Applications Of Sersmentioning
confidence: 99%
“…Solar energy conversion, catalysis, water treatment, antimicrobial activity, lithography and photocatalysis are studied by researchers to utilize functional features of AgNPs [15][16][17]. Some different approaches such as photochemical and electrochemical procedures, radiation, and Langmuir-Blodgett are currently widely used to synthesize AgNPs [18][19][20][21][22]. In the last two decades, the biological methods using microorganisms or plant extracts have been significantly considered.…”
Section: Introductionmentioning
confidence: 99%